Evaluation of Programs Medical Laboratory Technology - Setiawan, Heru; Syahrial, Zulfiati; Suparman , Atwi; Jarudin, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine and describe the implementation of the Acceleration Program for Improving the Qualification of the Diploma in Three Medical Laboratory Technology through Recognition of Past Learning towards improvement and refinement. This research is a program evaluation using an evaluative method based on the context input process and product evaluation model, which focuses on just one phenomenon selected and wants to be understood in depth by ignoring other phenomena. Respondents are managers of the Medical Laboratory Technology D-III Program, lecturers, students, and graduate user agencies. Data collection techniques in this study are adjusted to the data components sought by using interview techniques, questionnaires, and an inventory checklist. The evaluation of this study is the evaluation of lectures, which begins with the learning planning process, the implementation of learning, assessment of learning outcomes, and supervision of learning (Monev) in the Medical Laboratory Technology D-III Program. The results of the evaluation are expected to help the project leader or teacher make decisions regarding the continuation, end, or modification of the program. Product evaluation is related to the results of a program. This evaluation is a record of the achievement of results and decisions for improvement, implementation, or actualization. Evaluation activities are efforts to measure and interpret the results achieved. Measurements are developed and administered carefully and thoroughly. The accuracy of the analysis will be the material for drawing conclusions and submitting suggestions to what extent the product can be reached by the eligibility standards.